Modification of method of synthesis for adaptive gyropilot with the given dynamic error - Іванов, Сергій Вікторович; Тєут, Василь Михайлович; Олійник, Павло Борисович (Eastern-European Journal of Enterprise Technologies, 2012)
The article is dedicated to the problem of synthesis of gyropilot with given dynamic error based on the authors’ methods. The basis of the above-mentioned methods of synthesis is the bringing of the gyropilot characteristics to a reference system that has the desired properties. In the article the mentioned method was modified to simplify the structure of the regulator when receiving a given value of dynamic error and acceptable parameters of the transition process. To achieve the goal three options were offered: the creation of gyropilot with variable structure, the removal of the cutoff frequency for the eigenfrequency of the ship model, the direct compensation of exposure of time constant of the ship model. According to the results of study for the implementation in real devices the third option (direct compensation of time constant) was recommended, since its application provides a simplified structure of gyropilot compared with auto steering with variable structure and minimized overshoot and time of the transition process in the "gyropilot-ship "system compared with other options